2020
DOI: 10.3389/fcell.2020.550267
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning the TGFβ Signaling Pathway by SARA During Neuronal Development

Abstract: Neural development is a complex process that involves critical events, including cytoskeleton dynamics and selective trafficking of proteins to defined cellular destinations. In this regard, Smad Anchor for Receptor Activation (SARA) is an early endosome resident protein, where perform trafficking-associated functions. In addition, SARA is also involved in cell signaling, including the TGFβ-dependent pathway. Accordingly, SARA, and TGFβ signaling are required for proper axonal specification and migration of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…One study has shown that the depletion of SARA, or deletion of its SMAD Binding Domain (SBD) in endothelial cells, inhibited the transcriptional activity of both SMAD2 and SMAD3 in vitro [ 84 ], whereas a separate study has shown that SARA depletion in HeLa cells or Mv1Lu cells had little effect on these SMADs [ 64 , 85 ]. SARA was also shown to inhibit SMAD2/3 signaling in rat neural cells [ 86 ]. As alternatives to the targeting of TGFβ or TGFBR per se, different research groups have developed peptide aptamers of SARA SBD that have shown significant inhibition of SMAD2/3 signaling in human renal epithelial cells and mouse mammary gland cells [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown that the depletion of SARA, or deletion of its SMAD Binding Domain (SBD) in endothelial cells, inhibited the transcriptional activity of both SMAD2 and SMAD3 in vitro [ 84 ], whereas a separate study has shown that SARA depletion in HeLa cells or Mv1Lu cells had little effect on these SMADs [ 64 , 85 ]. SARA was also shown to inhibit SMAD2/3 signaling in rat neural cells [ 86 ]. As alternatives to the targeting of TGFβ or TGFBR per se, different research groups have developed peptide aptamers of SARA SBD that have shown significant inhibition of SMAD2/3 signaling in human renal epithelial cells and mouse mammary gland cells [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a wide consensus on the classification of these factors into positive and negative signals, promoting or restraining polarization. For instance, BDNF, insulin, IGF-1 and TFG-ß, among others, bind to their plasma membrane receptors triggering activation of intracellular signaling pathways favoring polarization ( Sosa et al, 2006 ; Arimura and Kaibuchi, 2007 ; Yi et al, 2010 ; Nakamuta et al, 2011 ; Takano et al, 2019 ; Rozés-Salvador et al, 2020 ). Most polarizing signals—if not all—are transduced by tyrosine kinase receptors (TRK) located at the plasma membrane, triggering the activation of the phosphatidylinositol 3 kinase (PI3K) and conversion of phosphatidylinositol 4,5 bi-phosphate (PIP2) into phosphatidylinositol 3,4,5 tri-phosphate (PIP3).…”
Section: Decoding Extrinsic Signals: the Role Of Trk Receptors Pi3k A...mentioning
confidence: 99%